ANALISIS TINGKAT DISINTEGRASI BATULANAU BERDASARKAN PENGUJIAN SLAKING INDEX DI KOTA SAMARINDA PROVINSI KALIMANTAN TIMUR: ANALYSIS OF THE DISINTEGRATION RATE OF BATULANAU BASED ON THE SLAKING INDEX TEST IN SAMARINDA CITY, EAST KALIMANTAN PROVINCE - Situmorang, Ardo P; Oktaviani, Revia; Dina Devi, Shalaho; Winarno, Agus; Juvensius Pontus, Albert (JURUSAN TEKNIK PERTAMBANGAN UPR, 2023)
Slaking is a rock behavior which when in direct contact with water and temperature often causes the destruction of particles, cracks and peeling of the surface layer of rock within a certain time. The purpose of this test was to observe the weathering and breakdown reactions of siltstone samples immersed in water in the Pulaubalang Formation and the Balikpapan Formation in the City of Samarinda, East Kalimantan Province. The research method was carried out quantitatively which produced values ​​which became the basis for determining the classification of the level of destruction of Batulanau. The siltstone samples will be classified at each level of destruction according to the level which is divided into 5 classes. From the results of testing 12 siltstone samples, the values ​​for the level of destruction 1 and 2 were obtained. Where the classification level of destruction 1 and 2 means that the rock samples tested experienced a fairly low level of disintegration or destruction due to the water immersion and drying processes. Keywords: Siltstone, Slaking Index, Disintegration Rate